Políticas e práticas sociais no processo formativo do trabalhador da educação de jovens e adultos: o presente, o vivido - Grisi, Eloide Teles Silva (2020)
This dissertation have as its general objective to analyze the training process of young and adult education workers (EJA), with a view to social policies and practices in the State of Paraíba, which involve this educational modality. The research sought to identify the positive and / or negative aspects presented by the students of EJA, and to identify the profile of these and these, in an educational institution in the State of Paraíba. The analysis of this research regarding the training process of EJA student workers, with a view to social policies and practices in the State of Paraíba, concomitant with the educational legislation to this modality, was presented in prospecting. Therefore, the hypothesis raised shows a potential for governmental negligence in the aspects of social practices in the training of these EJA student workers. The research, of qualitative characteristic, was carried out with the method of focus group and for analysis of the results the technique of the Discourse of the Collective Subject-DSC was used. Analyzing the speeches of the participants concomitant with the documents studied, focusing on the State of Paraíba, it was noticed factors relevant to social policies and practices in positive and negative aspects. The results of the research presented a wealth of information, because when giving voice to EJA students, who bring a wealth of experiences in contexts outside the classrooms, in their work, and with their families, we had a wealth of contributions presented with sincere information of their trajectories being created in the context of education by EJA, in the present to the lived. The research showed important results in the current context, because even in positive and conformist speeches, calls for help prevail in favor of a more just society, with basic conditions and access to Education for all, according to the right guaranteed by law. This research arouses even more provocations with a view to continuous improvement when the theme is the training of EJA student workers. Educational policies versus governance have been the subject of intermittent demands between encounters and mismatches, dilemmas and possibilities, because in our capitalist society, the interests of some are different from the interests of everyone.